STUDY ON THE DECISION OF JUDGE "NO.84 / PID-SUS /2017/PN.DONGGALAâ€ ABOUT NARCOTICS ABUSE - Buheli, Doddy Tisna Amijaya (Tadulako Master Law Journal, 2019)
The research problem was the legal consideration of judge in decide verdictforconvict based on court decisionnumber: 84/Pid-Sus/2017/PN. Donggala andlegal consequences of the conviction decision number: 84/Pid-Sus/2017/Donggala wereimposed on convicted person The objective of this research is to find out and to analyze the legal consideration of judge in decide verdictforconvict based on court decision number:84/Pid-Sus/2017/PN. Donggala and to find out and analyze the legal consequences of conviction decision imposed on convicted person. The research used normative research method and qualitative research type. The result of the research show that the consideration of judge in imposeconviction decision is based onverification in a case carried out by a claimant based on proven legal facts. Based on thedefendantstatements, witness statements and evidence, existing legal facts have proven to be legitimate and convincing guilty of committing a criminal act "Criminal Agreement without the Right to Submit Narcotics Group I in accordance with consideration of juridical and non-juridical and legal consequence with the verdict conviction of the defendant in a narcotics crime, namely: conviction and fines on the defendant and reduced punishment while serving detentionand confiscation of evidence. The prosecutor and defendantmay submit an appeal attempt strengthened by the decision. It is recommended for the panel of judges to impose a punishment onthe defendant must have confidence that the defendant is legally and convincingly committing a crime based on the evidence that follow the justice process, prioritizing the instrumentsand systemof evidence or facts revealed at the justice impose maximum criminal sanctions on the defendant as a deterrent effect.